From fragrance to ecosystems - exploring the traditional medicine and socio-economic-cultural heritage of Pandanus odorifer (Forssk.) Kuntze: A review - Panda, Taranisen; Mishra, Nirlipta; Rahimuddin, Shaik; Pradhan, Bikram; Mohanty, Raj Ballav (Ethnobotany Research and Applications, 2024)
Background: Pandanus odorifer (Forssk.) Kuntze, known as kewda, is a widely distributed plant species in tropical regions. This article explores the botanical features, traditional applications, and the socio-cultural and economic significance of P. odorifer. Methods: The methodology involved an extensive search of peer-reviewed literature, scientific databases, and relevant sources to compile data on diverse attributes of P. odorifer. Results: The Paleotropical monocot family Pandanaceae includes approximately 700 species spread across five genera: Pandanus Parkinson, Freycinetia Gaudich., Martellidendron (Pic. Serm.) Callm. & Chassot, Sararanga Helms, and Benstonea Callm. & Buerki. Of the five genera: three (Pandanus, Benstonea, and Freycinetia) are found in India. The unique morphology and ecological adaptations of Pandanus odorifer contribute to its widespread distribution and resilience. Additionally, it possesses aromatic and medicinal properties. Rich in phytochemicals like lignans, isoflavones, and alkaloids, alongside essential nutrients, it offers therapeutic and nutritional benefits. The oil extracted from its male flowers, containing phenylethyl methyl ether, finds applications in various industries such as aromatherapy, cosmetics, and food. Traditional medicinal practices utilize P. odorifer for treating headaches, inflammation, and colds, among other ailments. It also holds cultural significance and is utilized in handicrafts and as a flavoring agent. Conclusions: Pandanus odorifer is a valuable botanical resource with significant ecological, cultural, and economic importance. Its traditional uses and diverse chemical composition demonstrate its multifunctionality. Continued research and conservation are essential to harness its potential for sustainable development and ensure its survival amid environmental changes. Keywords: Ethnic utility, Kewda, Pandanaceae, Phytochemical constituents, Therapeutic applications